CCTV - lamp camera for smart home solution - Reginald Tannor (ХНУРЕ, 2020)
The report contains the results of a study of the communication quality parameters of a remote wireless channel for controlling a lamp as a remote access for monitoring the security status of a home, workplace or company. Closed Circuit Television Cameras (CCTV) have become an important crime prevention and security measure. Cameras collect images and transfer them to a monitoring-recording device where they are available to be watched, reviewed and/or stored.